Review of the discard and/or refusal rate of offered donor hearts to pediatric waitlisted candidates. (21st March 2020) - Schweiger, Martin; Everitt, Melanie D.; Chen, Sharon; Nandi, Deipanjan; Castro, Javier; Gupta, Dipankar; Scheel, Janet; Lal, Ashwin K.; Ablonczy, Laszlo; Kirk, Richard; Miera, Oliver; Davies, Ryan R.; et al.
Abstract: We aimed to review current literature on the discard rate of donor hearts offered to pediatric recipients and assess geographical differences. Consequences and ways to reduce the discard rate are discussed. A systemic review on published literature on pediatric transplantation published in English since 2010 was undertaken. Additionally, a survey was sent to international OPOs with the goal of incorporating responses from around the world providing a more global picture. Based on the literature review and survey, there is a remarkably wide range of discard and/or refusal for pediatric hearts offered for transplant, ranging between 18% and 57% with great geographic variation. The data suggest that that the overall refusal rate may have decreased over the last decade. Reasons for organ discard were difficult to identify from the available data. Although the refusal rate of pediatric donor hearts seems to be lower compared to that reported in adults, it is still as high as 57% with geographic variation.